2020
DOI: 10.1101/2020.06.25.20139725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GWAS of Retinal Vessel Tortuosity Identifies 173 Novel Loci Revealing Genes and Pathways Associated with Vascular Pathomechanics and Cardiometabolic Diseases

Abstract: Fundus pictures of the eye allow for non-invasive inspection of the microvasculature system of the retina which is informative on cardiovascular health. Automated image processing enables the extraction of morphometric properties of this system as quantitative features that can be used for modelling disease risks. Here we report the results of the largest genome-wide association study (GWAS) of retinal vessel tortuosity conducted to date using data from the UK Biobank (N=63,899). We identified 87 loci associa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 164 publications
(374 reference statements)
3
7
0
Order By: Relevance
“…The direction of these estimates agrees with their phenotypical correlations and published papers 6 , suggesting a partial explanation by their common genetic basis. This finding agrees with three aforementioned studies 11,14,41 which identified novel retinal width and tortuosity loci associated with CAD but did not estimate a genetic correlation between retinal phenotypes and CAD. In summary, our analysis characterises the genetic architecture of D f and highlights a common genetic basis with cardiovascular diseases, which partly explains the inverse association between D f and coronary vessels dysfunction.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The direction of these estimates agrees with their phenotypical correlations and published papers 6 , suggesting a partial explanation by their common genetic basis. This finding agrees with three aforementioned studies 11,14,41 which identified novel retinal width and tortuosity loci associated with CAD but did not estimate a genetic correlation between retinal phenotypes and CAD. In summary, our analysis characterises the genetic architecture of D f and highlights a common genetic basis with cardiovascular diseases, which partly explains the inverse association between D f and coronary vessels dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…The SNP heritability (h 2 SNP) of the left and right Df estimate are respectively 0.09 (0.015) and 0.10 (0.014). These h 2 SNP magnitude is in line with previous results from retinal vascular tortuosity 11,14 , retinal width 12 , and the recently published Df 26 GWAS.…”
Section: Gwas Reveals Nine Fractal Dimension Loci and Their Association With Cardiovascular Risk Factorssupporting
confidence: 91%
See 2 more Smart Citations
“…76 It was also suggestively associated with vascular FD (β, −0.069 SD; P =1.06×10 − 7 ). Further sensitivity analyses and comparison with variants identified in a previous GWAS of vascular tortuosity 24 are provided in the Supplemental Results (Figure S13 and S14 and Table S12).…”
Section: Resultsmentioning
confidence: 99%